27 UMPSA student leaders promise to shoulder responsibilities - Siti Nur Azwin, Zulkapri (UMPSA, 2024)
KUANTAN, 11 January 2023 - A total of 27 students pledged and signed the oath of the Students’ Representative Council (MPP) of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) Session 2023/2024 before the Vice-Chancellor, Professor Dato’ Ts. Dr. Yuserrie Zainuddin at the ceremony held at Swiss-Belhotel Kuantan.